2022
DOI: 10.1183/23120541.00014-2022
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids and COVID-19 outcomes in asthma: the Israeli experience

Abstract: Inhaled corticosteroids (ICS) alone or in combination with bronchodilators are widely used in asthma [1]. ICS have potential immunosuppressive effects which may promote viral replication, delayed viral clearance and increased risks of secondary infections [2, 3]. Furthermore, ICS use in asthma is associated with an increased risk of upper respiratory tract infections [2, 3]. Therefore, in the face of the current coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome-coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…26,27) However, ICS can be safely used in patients with asthma even during the COVID-19 pandemic and SARS-CoV-2 infection. 28) Several studies have reported that patients aged 16-49 years using ICS with or without long acting βagonists do not carry an increased risk for COVID-19-related in-hospital mortality. 19) The proportion of ICS usage in adult asthma patients is significantly lower among those who are hospitalized due to A c c e p t e d A r t i c l e its use to treat COVID-19 itself.…”
Section: Effect Of Asthma Medications On Clinical Outcomes Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…26,27) However, ICS can be safely used in patients with asthma even during the COVID-19 pandemic and SARS-CoV-2 infection. 28) Several studies have reported that patients aged 16-49 years using ICS with or without long acting βagonists do not carry an increased risk for COVID-19-related in-hospital mortality. 19) The proportion of ICS usage in adult asthma patients is significantly lower among those who are hospitalized due to A c c e p t e d A r t i c l e its use to treat COVID-19 itself.…”
Section: Effect Of Asthma Medications On Clinical Outcomes Of Covid-19mentioning
confidence: 99%
“…However, concern exists regarding whether ICS use is associated with an increased risk of susceptibility to SARS-CoV-2 infection or severe COVID-19 due to the potential immunosuppressive effects of ICS through increased susceptibility to secondary infection, viral replication promotion, and delayed viral clearance [ 26 , 27 ]. However, ICS can be safely used in patients with asthma even during the COVID-19 pandemic and SARS-CoV-2 infection [ 28 ]. Several studies have reported that patients aged 16–49 years using ICS with or without long-acting β-agonists do not carry an increased risk for COVID-19-related in-hospital mortality [ 19 ].…”
Section: Asthmamentioning
confidence: 99%
“…In a recent article in ERJ Open Research , A dir et al . [ 23 ] analysed the association between ICS treatment and COVID-19 prognosis, evaluating SARS-CoV-2 infection based on a positive PCR, moderate–severe COVID-19 incidence, and mortality, but did not observe any meaningful relationship between ICS treatment and the assessed outcomes. The studies available, which analyse the association of this treatment with the prognosis of asthma patients with COVID-19, offer conflicting results.…”
mentioning
confidence: 99%
“…When it comes to ICS treatment, some authors report a worse evolution [ 24 , 25 ], others a better one [ 26 , 27 ], and in the remainder, coinciding with the results of A dir et al . [ 23 ], no relevant impact has been shown [ 9 , 12 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation